The problem of forming the professional and ethical culture in psychological and pedagogical literature - Prokhorchuk, Polina (Professional Pedagogics, 2018)
Mastering the norms of general and professional culture are presented in the article as important qualities of a modern specialist, necessary for the successful development of his personal and professional career. The necessity to develop these qualities in the process of future graphic designers’ professional training as specialists with professional activity connected with graphic art, aimed to create and operate visual art images, is grounded. The content analysis of the concepts of “professional culture” and “pedagogical conditions” is made. It is mentioned that various definitions of the mentioned concepts exist in the modern scientific and pedagogical literature. The modern researchers’ different views on defining the concept of “pedagogical conditions of forming the professional and ethical culture” essence are shown. It was found that this pedagogical phenomenon is explained mainly as: a set of actions aimed at stage-by- stage modelling and effective functioning of the process forming and developing the sufficient level of professional and ethical culture; the process of personality’s formation as a result of the objective influence of heredity, environment, education (upbringing), self-education and pedagogical management of human person’s individual formation. By analysing the psychological and pedagogical literature the main pedagogical conditions are characterised; they ensure the process of forming the professional, ethical, moral, and professional and ethical culture. Summarizing the scientists’ views made it possible to conclude that the most suitable for organizing the future graphic designers’ professional training can be: improving the knowledge about the mechanisms of creative self-development; using the innovational technologies for professional skills forming...
Keywords: pedagogical conditions; professional and ethical culture; professional career; self-development; motivation